ANALISIS MOTIVASI EKSTRINSIK PETANI DALAM MENABUNG DI BANK RAKYAT INDONESIA (BRI) UNIT UKUI KECAMATAN UKUI KABUPATEN PELALAWAN - Rizal Rizal; Evy Maharani; Eliza Eliza (Jurnal Ilmiah Pertanian, 2016)
The purpose of this research is to motivation extrinsic analysis of the farmers in saving money in ukui unit bank rakyat indonesia (BRI). This article discusses about the extrinsic motivation of farmers in saving money in Ukui Unit BRI. This research is using interview method 86 selected sample by questionnaire. The data source used are primary data using a Likert's Summated Rating Scale (SLRs). This research was conducted in BRI Unit Ukui at Jalan Lintas Timur Ukui in Sub-District of Ukui, Pelalawan, and started from March 2015-August 2016. The results showed that the average of the extrinsic motivation of farmers in save in Ukui Unit BRI consisting of a service, product, promotion, interest and location are categorized as "high" with a score of 3.66. With respective scores are 4.06 for service categorized as "high", 3.51 for the products categorized as "high", 3.52 for promotion categorized as "high", 3.53 for interest categorized as "high" and 3.70 for location categorized as "high".